'Meltdowns', surveillance and managing emotions; going out with children with autism - Ryan, S (Elsevier, 2010)
The qualitative study from which the data reported here are taken, explored the experiences, support and information needs of parents of children diagnosed with autism spectrum disorders. 46 parents were interviewed either individually or in couples. Thematic analysis of the data revealed the complexity involved for the parents in taking their children out in public places. The emotion work parents conduct in public places both to make their children more acceptable within the space and to reduce the discomfort that others experience, helps to preserve the orderliness of public places. However, the special competence that parents developed over time also masks their turbulent feelings in public encounters.